# Answer to Question #33988 in Statistics and Probability for rohini chandrakant chuadhari

Question #33988

if f(x)=a raise to x,a>0,show that

f(x+1)=a*f(x)=f(2)*f(x-1)

f(x+1)=a*f(x)=f(2)*f(x-1)

Expert's answer

We have

f(x+1)=a

For the second equality we have

f(2)*f(x-1)=a

QED.

f(x+1)=a

^{x+1}=a*a^{x}=a*f(x) - this is the fist equalityFor the second equality we have

f(2)*f(x-1)=a

^{2}a^{x-1}=a*(a*a^{x-1})=a*a^{x}=a*f(x).QED.

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment